Plantation crops-based farming system is remunerative - Raramesh, V; Chakurkar, E B (Indian Horticulture, 2019)
The integrated farming system (IFS) is a judicious mix of one or more enterprises along with cropping having complimentary effect through effective recycling of wastes and crop residues and encompasses additional source of income to the farmers. The IFS activity depends on inter-dependent, inter-related and interlinking production systems, based on crops, animals and related subsidiary professions. It improves species diversity, helps in soil building, preserving and improving ecological condition essential to achieve sustainability. It also enhances soil-nutrient cycling and prevents proliferation of pests. In all the ecosystems, IFS approach with location-specific models offers gainful employment and is highly profitable and sustainable. In this regard, the wide interspace between plantation crops can be efficiently used to grow variety of crops and to sustain the farmer’s income and reduce the risk of crop failure and market fluctuations. Along with IFS, the soil and water conservation, integrated nutrient management, agroforestry, increase in nutrient-use efficiency processing and value addition are need of the hour.